PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BAGIAN UMUM PADA SEKRETARIAT DAERAH KABUPATEN ROKAN HILIR - Anuar, Saipul (Eko dan Bisnis: Riau Economic and Business Review, 2019)
A leader plays an important role in running and organizing an institution. A leader is a key person to make an institution will be a great institution . The role of a leader in an organization or group is vital. Because in that role, a leader will help the organization to realize its vision and mission. the purpose of this research can be formulated as follows: To determine the influence of Leadership on Performance of Administration Staff at district secretariat office at Rokan Hilir District. This is a descriptive quantitative research, which describes the relationship between variables to analyze numerical data using statistical methods through hypothesis testing. In this study took the entire population of employees at district secretariat office at Rokan Hilir District which consists of 37 people. Results of simple correlation analysis showed that the leadership role positively and significantly correlated to the performance of an employee or significant influence with the power of 79.8%; meaning that developments in performance of 79.8% is determined or influenced by the leadership role